MARKETING RESEARCH OF ATTRACTING INVESTMENTS IN HUMAN CAPITAL OF THE SPHERE OF CREATIVE INDUSTRIES OF THE IVANO-FRANKIVSK TC - Blahun, I. I. (The actual problems of regional economy development, 2024)
The article examines the attraction of investments in human capital in the creative industries of Ivano-Frankivsk TC, analyzes the classification of economic activities included in the list of creative industries. The purpose of the article is to study investments in educational programs that train specialists in the creative industries. In the course of the study, desk research was used, as well as the methods of abstraction, generalization and comparative analysis. It has been determined that the largest set of educational programs that forms specialists in the field of creative industries is in the field of 02 Culture and Arts. The results of the study made it possible to identify the educational programs with the highest level of investment. An analysis of recent research and publications on this topic makes it possible to understand that in the face of instability, creative industries can become a driver of TC development. The investment potential of creative industries consists of both internal and external resources. The article analyzes the costs of applicants who have invested in educational programs that provide employment opportunities in the creative industries. The number of applicants enrolled in arts and culture specialties deserves attention. The fluctuation of the audience and its involvement is inherent in both public and private universities. In addition, it is worth noting the level of investment in education for each educational program. It also shows the correspondence between the number of students in each educational program. The educational programs with the highest number of students are identified. In general, it is worth noting that the investment assessment of human capital in the educational dimension provides an opportunity for development in a creative environment. This area is in the process of constant transformation and development, and will be the subject of ongoing research by both scientists and businesses that promote their products or services in the digital environment. The study of attracting investments in human capital in the creative industries of Ivano-Frankivsk TC is of practical importance in the field of creative industries, as it makes it possible to analyze the attraction of investments in the educational segment of the creative industries. The role and place of investment in education in the structure of investment in the creative industries will continue to grow. Firms will resort to a constant search for personnel in the field of culture and art. After all, the indicator of engagement of applicants' activity has a constant impact on other factors of the cultural environment. This, in turn, forms the investment climate in the field of educational services, which directly affects the investment climate of creative products, determining their place in comparison with other products in the structure of the TC economy.